Inovasi Kegiatan Masa Kini Perpustakaan Kafe Literacy Coffee - Nur'aini Nur'aini (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The Cafe Library is a library designed with coffee shops and books. The cafe library provides more value to visitors and provides a place of comfort for visitors who come so they don't feel bored to the library. The cafe library can be used as an innovative alternative as a place for recreation/educational tourism. One of the functions of the library is a place of recreation for the community. Libraries are required to play an active, innovative and creative role to make the visitors who come can feel happy and satisfied. The layout of the space needs to be considered in order to increase the role of the library as a place of recreation and a vehicle for education for the wider community. To make the library a place of recreation and a vehicle for education for visitors/communities who come, it is necessary to have innovations carried out in the form of activities or services made by library managers. The purpose of this study is to find out the innovations of contemporary activities carried out by the literacy coffee cafe library. This research takes place in the literacy coffee cafe library. This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out by means of observation, interviews, and documentation. Data reduction, data presentation and conclusion/data verification are data analysis of this research. The results of this study show that literacy coffee cafe library managers develop innovative activities for visitors/communities who come. Various innovative activities carried out in the literacy coffee cafe library such as general discussions, political discussions, book reviews, film reviews, and film classes. This research is expected to be a reference for other cafe libraries to develop or improve innovative activities so that visitors/communities feel at home visiting literacy coffee.